2009
DOI: 10.1159/000257228
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Endoscopic Microsurgery for Local Excision of Rectal Lesions: Is There a Learning Curve

Abstract: Background: Transanal endoscopic microsurgery (TEM) is a minimally invasive technique for the local resection of benign and stage T1 rectal lesions in selected patients, associated with lower morbidity and mortality rates than open surgery. We present our initial results and assess whether experience influences outcome after TEM. Methods: This was a prospective descriptive survey. All patients undergoing TEM for tubulovillous adenoma or carcinoma between 2002 and 2007 were included. Results: A total of 105 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 37 publications
0
28
0
1
Order By: Relevance
“…14,17 Also, a number of studies have reported significantly decreased duration of surgery for TEM compared with radical resection, with reductions ranging from 46 to 140 minutes. Most patients who undergo TEM experience short hospital stay and early return to routine activities, even after resection of very large lesions, often with full thickness excision.…”
Section: Duration Of Surgery Length Of Stay and Costmentioning
confidence: 99%
“…14,17 Also, a number of studies have reported significantly decreased duration of surgery for TEM compared with radical resection, with reductions ranging from 46 to 140 minutes. Most patients who undergo TEM experience short hospital stay and early return to routine activities, even after resection of very large lesions, often with full thickness excision.…”
Section: Duration Of Surgery Length Of Stay and Costmentioning
confidence: 99%
“…Study by Heintz et al is difficult to interpret due to inclusion of patients who had inadequate local surgery. TEM is a safe technique with low morbidity and recurrence rates (Koebrugge et al, 2009). Experience over times has led to a reduction in operation time, length of patients' hospital stay and complication rate.…”
Section: Transanal Resection (Tar) / Transanal Endoscopic Microsurgermentioning
confidence: 99%
“…TEM has also become a valuable option in selected patients with malignant rectal disease, in whom it may provide an acceptable oncological outcome with minimal postoperative morbidity and an improved functional outcome compared with standard radical resection (8,9). However, nearly 30 years after the introduction of TEM, this transanal platform has not achieved widespread adoption due to the cost and the complexity of the instruments, the steep learning curve and the requirement of specialized training to master the operation (10,11).…”
Section: Introductionmentioning
confidence: 99%